Cross-linked enzyme aggregates (CLEAs): Stable and recyclable biocatalysts - Sheldon, R.A. (author) (Portland Press, 2007)
The key to obtaining an optimum performance of an enzyme is often a question of devising an effective method for its immobilization. In the present review, we describe a novel, versatile and effective methodology for enzyme immobilization as CLEAs (cross-linked enzyme aggregates). The method is exquisitely simple (involving precipitation of the enzyme from aqueous buffer followed by cross-linking of the resulting physical aggregates of enzyme molecules) and amenable to rapid optimization. We have shown it to be applicable to a wide variety of enzymes, including, in addition to a wide variety of hydrolases, lyases, e.g. nitrile hydratases and oxynitrilases, and oxidoreductases such as laccase and galactose oxidase. CLEAs are stable, recyclable catalysts exhibiting high catalyst productivities. Because the methodology is essentially a combination of purification and immobilization into one step, the enzyme does not need to be of high purity. The technique is also applicable to the preparation of combi-CLEAs, containing two or more enzymes, for use in one-pot, multistep syntheses, e.g. an oxynitrilase/nitrilase combi-CLEA for the one-pot conversion of benzaldehyde into (S)-mandelic acid, in high yield and enantiomeric purity. Biotechnology Applied Sciences